# Solve Using the Square Root Property x^2+6x-6=0 x2+6x-6=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=6, and c=-6 into the quadratic formula and solve for x.
-6±62-4⋅(1⋅-6)2⋅1
Simplify.
Simplify the numerator.
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-6±36-4⋅-62⋅1
Multiply -4 by -6.
x=-6±36+242⋅1
Add 36 and 24.
x=-6±602⋅1
Rewrite 60 as 22⋅15.
Factor 4 out of 60.
x=-6±4(15)2⋅1
Rewrite 4 as 22.
x=-6±22⋅152⋅1
x=-6±22⋅152⋅1
Pull terms out from under the radical.
x=-6±2152⋅1
x=-6±2152⋅1
Multiply 2 by 1.
x=-6±2152
Simplify -6±2152.
x=-3±15
x=-3±15
Simplify the expression to solve for the + portion of the ±.
Simplify the numerator.
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-6±36-4⋅-62⋅1
Multiply -4 by -6.
x=-6±36+242⋅1
Add 36 and 24.
x=-6±602⋅1
Rewrite 60 as 22⋅15.
Factor 4 out of 60.
x=-6±4(15)2⋅1
Rewrite 4 as 22.
x=-6±22⋅152⋅1
x=-6±22⋅152⋅1
Pull terms out from under the radical.
x=-6±2152⋅1
x=-6±2152⋅1
Multiply 2 by 1.
x=-6±2152
Simplify -6±2152.
x=-3±15
Change the ± to +.
x=-3+15
x=-3+15
Simplify the expression to solve for the – portion of the ±.
Simplify the numerator.
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-6±36-4⋅-62⋅1
Multiply -4 by -6.
x=-6±36+242⋅1
Add 36 and 24.
x=-6±602⋅1
Rewrite 60 as 22⋅15.
Factor 4 out of 60.
x=-6±4(15)2⋅1
Rewrite 4 as 22.
x=-6±22⋅152⋅1
x=-6±22⋅152⋅1
Pull terms out from under the radical.
x=-6±2152⋅1
x=-6±2152⋅1
Multiply 2 by 1.
x=-6±2152
Simplify -6±2152.
x=-3±15
Change the ± to -.
x=-3-15
x=-3-15
The final answer is the combination of both solutions.
x=-3+15,-3-15
The result can be shown in multiple forms.
Exact Form:
x=-3+15,-3-15
Decimal Form:
x=0.87298334…,-6.87298334…
Solve Using the Square Root Property x^2+6x-6=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top